IMPLEMENTATION OF INTEGRATED ADMINISTRATIVE SERVICES (PATEN) IMPROVING THE QUALITY OF PUBLIC SERVICES IN WONOAYU DISTRICT, SIDOARJO REGENCY - Mutrafidah, Rizky Marriery; Mursyidah, Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study examines the implementation of e-government through the Integrated Sub-district Administrative Services (Pelayanan Administrasi Terpadu Kecamatan/PATEN) system, which delivers services in a single location from application submission to document completion. Method: Employing a qualitative descriptive approach, data were collected through observation, documentation, and interviews with PATEN staff, the head of PATEN in Wonoayu Subdistrict, and members of the public utilizing the services. The purposive sampling method was applied, and data analysis followed the Miles and Huberman model, involving collection, reduction, analysis, and conclusion. Results: The findings reveal that while the PATEN system has streamlined administrative processes, challenges remain in providing adequate waiting facilities and human resources that fully meet community needs. Novelty: This research contributes to the discourse on e-government by offering empirical evidence on PATEN’s practical implementation at the sub-district level, highlighting both its strengths in service integration and its limitations in resource allocation, thereby providing insights for enhancing local governance and improving citizen satisfaction.